2009
DOI: 10.2134/agronj2008.0150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fungicide on Soybean Growth and Yield

Abstract: In response to rising input costs and narrowing profi t margins, soybean [Glycine max (L.) Merr.] producers are continually looking for ways to increase soybean yield. One approach being promoted is the use of foliar fungicides, for both foliar pathogen control and nonfungicidal plant physiological eff ects. Th e objective of this fi eld experiment was to evaluate a strobilurin and a triazole alone or in combination on soybean in the absence of foliar diseases to determine the potential eff ect on soybean grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
79
6
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 19 publications
13
79
6
4
Order By: Relevance
“…Based on previous studies, soybean seed germination rate (SGR) could be reduced by seed disease occurrence caused by soil-borne pathogens [37]- [42]. In our untreated and fungicide-treated seed tests without application of flooding, our results showed that fungicide treatment significantly increased soybean seed germination rate (SGR) in the field.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Based on previous studies, soybean seed germination rate (SGR) could be reduced by seed disease occurrence caused by soil-borne pathogens [37]- [42]. In our untreated and fungicide-treated seed tests without application of flooding, our results showed that fungicide treatment significantly increased soybean seed germination rate (SGR) in the field.…”
Section: Discussionsupporting
confidence: 56%
“…Apron Maxx RTA (Syngenta Crop Protection Inc.) is a broad-spectrum fungicide widely used in the United States for seed treatment, and can control or suppress pathogens Phomopsis, Pythium, Phytophthora, Rhizoctonia, and Fusarium [42]. However, it is still unknown if this fungicide can maintain soybean seed survival and improve seed germination in the flood-affected field.…”
Section: Introductionmentioning
confidence: 99%
“…Since the motion of most fungicides is acropetal (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011 andLENZ et al 2011), spraying the base of plants suggests significantly a more effective control of the diseases when compared to sprayings by tips distant from the apex of soybean plants. However, experimental results indicate that the aggregation of such technology in aerial spraying of fungicide from soybean -isolated or in combination with conventional sprayings -did not differ significantly from the spraying by nozzles on the culture; thus refuting the assumptions that justify the use of such technology application.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, it is here that the coverage and penetration of the fungicide are more adversely affected by the leaf weight of tops to form a barrier spraying, favoring the pathogen (ALMEIDA et al 2,005;CALLA et al 2,009;REIS et al, 2010;CUNHA et al, 2011). Like most systemic fungicides suitable for chemical control of soybean foliar diseases move in the direction of the base to the apex of the plant, the leaves of the lower third of the plant become the target of spraying (SWOBODA & PEDERSEN, 2009;ANTUNIASSI et al, 2011;LENZ et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Present, higher yielding soybean production systems typically use lower planting densities and in some cases wider row spacing (e.g., 76 cm) with improved fertilizer source and placement technologies. Grain producers have also realized gains in biomass production and in some cases yield resulting from insecticide and fungicide use (Bradley and Sweets, 2008;Bradshaw et al, 2008;Swoboda and Pedersen, 2009). Th ese more commonly used agronomic practices accompanied by improved varieties may favor nutrient uptake during diff erent key growth stages than originally thought.…”
Section: Soybean Yields In the United States Have Averagedmentioning
confidence: 99%